Noninvasive pulse oximeter: a contribution of literature to medicine (Research, Society and Development, 2020)
The pulse oximeter is a technological advance that allows the continuous and non-invasive monitoring of oxygen saturation in arterial blood, and is used as another tool in neonatal screening and presents itself as a possibility in reducing the incidence of mortality and severity of pathological complications. This is a bibliographic research with a qualitative approach, with the objective of describing the physiology and transport of blood, referring to the functioning of the pulse oximeter and also highlighting, based on the literature, diseases related to blood oxygenation. After the association of all descriptors, only 10 articles were selected. In view of this, literature was sought that could contribute to the achievement of the objectives proposed by the article, choosing not to establish a time frame for the books and, thus, 10 authors were used. After reflective reading, three categories emerged: Physiology and Oxygen Transport; Operation of the Pulse Oximeter; Diseases related to Blood Oxygenation The operation of the pulse oximeter is based on the different levels of light absorption for oxyhemoglobin and deoxyhemoglobin in the different lengths from where they are used in pulse oximetry. Disorders related to the breathing mechanism can cause serious damage to the individual's health, causing, in many cases, death, mainly due to the lack of oxygenation of the tissues to carry out their metabolic activities. It is concluded that, according to the results, it was found that the evaluation of pulse oximetry is a non-invasive, continuous, beneficial and applicable measure in patient care and also, a contribution to medical diagnoses.